2020
DOI: 10.4317/medoral.23448
|View full text |Cite
|
Sign up to set email alerts
|

What is the preferred concentration of ethanolamine oleate for sclerotherapy of oral vascular anomalies?

Abstract: Background This study compared three different concentrations of EO (1.25%, 2.5% and 5%) for the treatment of oral vascular anomalies (OVAs). Material and Methods This was a retrospective comparative analysis of patients with OVAs treated with EO. Anomalies smaller than 20 mm were included. The patients were treated with 1.25% (G1), 2.5% (G2), and 5% (G3) and clinical data were obtained. The number of sessions, the final volume and dose of EO were statistically analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
4
0
4
Order By: Relevance
“…Monoethanolamine oleate produces a dose‐dependent inflammatory response, resulting in fibrosis and possible vascular occlusion 25 Kato et al 26 evaluated the treatment of oral lesions with monoethanolamine oleate at concentrations of 1.25%, 2.5% and 5%. The concentration at 5% showed better performance, requiring fewer sessions and lower final volume.…”
Section: Discussionmentioning
confidence: 99%
“…Monoethanolamine oleate produces a dose‐dependent inflammatory response, resulting in fibrosis and possible vascular occlusion 25 Kato et al 26 evaluated the treatment of oral lesions with monoethanolamine oleate at concentrations of 1.25%, 2.5% and 5%. The concentration at 5% showed better performance, requiring fewer sessions and lower final volume.…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al stated that a single puncture may not be enough to dissipate the agent throughout the lesion, which suggests the need for varied punctures to allow the medication to reach the lesion in all its extension and depth [13]. Kato et al [14] showed that the concentration of 5% Ethamolin® performed better than 1.25% and 2.5% for sclerotherapy of oral vascular lesions measuring up to 20mm.…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que por mais que o HEM trate-se de uma lesão benigna, em alguns casos, pode ocasionar a compressão das estruturas adjacentes, ulceras e infecções secundárias. Cabendo ao profissional a atenção necessária para o diagnóstico e o tratamento (KATO et al, 2020).…”
Section: Fonte: Acervo Do Autorunclassified
“…Apesar da literatura apontar para possíveis efeitos adversos, como: necrose, dor e ulceração, no uso do oleato de monoetanolamina 5% sem diluição, nenhuma dessas condições foram observadas neste caso relatado. Esta terapêutica apesar de ir de encontro à diversos estudos, apresenta suporte científico na pesquisa mais recente de Kato et al (2020), estes autores utilizam o Ethamolin com e sem diluição em 30 pacientes e demonstraram que o uso desta substância sem diluição apresenta melhores resultados e efeitos adversos similares aos que são apresentados no uso deste composto diluído na aplicação intralesional em hemangiomas menores que 20mm.…”
Section: Fonte: Acervo Do Autorunclassified
See 1 more Smart Citation